Genome-wide microRNA Expression Profiling in Primary Tumors and Matched Liver Metastasis of Patients with Colorectal Cancer - Vychytilova-Faltejskova, Petra; Pesta, Martin; Radova, Lenka; Liska, Vaclav; Daum, Ondrej; Kala, Zdenek; Svoboda, Marek; Kiss, Igor; Slaby, Ondrej (Cancer genomics & proteomics, 2016)
BACKGROUND: Primary tumor spread to the liver is the major cause of disease progression and death in patients with colorectal cancer (CRC). MicroRNAs (miRNAs) are small non-coding RNAs that are involved in cancer development and progression, but their role in metastasis has not been extensively investigated. MATERIALS AND METHODS: Firstly, expression profiling of 752 miRNAs in 20 primary tumors and their corresponding liver metastases was performed. Secondly, validation of the results was carried out on an independent cohort of 66 patients with metastatic CRC using reverse transcription-quantitative polymerase chain (RT-qPCR) reaction. RESULTS: In total, 33 miRNAs were found to be significantly deregulated in liver metastases compared to their primary tumors. Fifteen miRNAs were chosen for subsequent validation, which confirmed significantly reduced expression of miR-143, miR 10b, and miR-28-5p, and increased expression of miR 122, miR-122*, and miR 885-5p in the tissue of liver metastases. CONCLUSION: These results indicate that miRNAs could serve as new therapeutic targets in patients with metastatic CRC.
Keywords: celogenomová asociační studie; nádory jater; regulace genové exprese u nádorů; Humans; lidé středního věku; MicroRNAs; microRNA; Female; Aged; dospělí; Cluster Analysis; senioři; lidé; Liver Neoplasms; reprodukovatelnost výsledků; Adult; ženské pohlaví; kolorektální nádory; Male; Reproducibility of Results; Middle Aged; Colorectal cancer; stanovení celkové genové exprese; transkriptom; shluková analýza; Aged, 80 and over; Genome-Wide Association Study; Transcriptome; senioři nad 80 let; mikro RNA; Gene Expression Profiling; mužské pohlaví; Gene Expression Regulation, Neoplastic; liver metastasis; Colorectal Neoplasms